2017
DOI: 10.1161/circulationaha.116.025760
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Aspirin for Primary Prevention of Cardiovascular Events in Patients With Type 2 Diabetes Mellitus

Abstract: Background: The long-term efficacy and safety of low-dose aspirin for primary prevention of cardiovascular events in patients with type 2 diabetes mellitus are still inconclusive. Methods: The JPAD trial (Japanese Primary Prevention of Atherosclerosis With Aspirin for Diabetes) was a randomized, open-label, standard care–controlled trial examining whether low-dose aspirin affected cardiovascular events in 2539 Japanese patients with type 2 diabetes mell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(84 citation statements)
references
References 46 publications
2
74
1
4
Order By: Relevance
“…Among 1 441 searched articles, we identi ed 26 studies for full-text review, of which 14 studies were eligible for qualitative and quantitative analyses (Appendix Figure S1). The 14 included studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] encompassed a total of 163 840 patients and used intention-to-treat principles. The detailed study characteristics are summarized in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among 1 441 searched articles, we identi ed 26 studies for full-text review, of which 14 studies were eligible for qualitative and quantitative analyses (Appendix Figure S1). The 14 included studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25] encompassed a total of 163 840 patients and used intention-to-treat principles. The detailed study characteristics are summarized in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The detailed study characteristics are summarized in Table 1. Two studies 13,17 were conducted in America, 6 studies were conducted in Europe (5 12,14,18,20,23 in the UK and 1 16 in Italy), 3 studies 19,21,22 were performed in Japan, and 3 studies 15,24,25 were performed in multiple nations. The comparator treatment was a placebo group in 9 studies 13-15, 17, 18, 20, 23-25 and was a no aspirin group in 5 studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Platelets can also undoubtedly trigger the onset of arterial thrombosis in response to atherosclerotic plaque rupture [28]. Moreover, although an in vitro study reported that platelet response to aspirin did not differ by diabetes status [29], there are data suggesting a reduction in the cardioprotective bene ts of aspirin in patients with diabetes [30], raising concerns about "aspirin resistance". These observations can be attributed to a number of factors, including increased platelet turnover rates in DM patients, suggesting that alternative aspirin dosing regimens (i.e., twice daily, the ANDAMAN trial, NCT02520921) or formulations be used [31][32][33].…”
Section: List Of Abbreviationsmentioning
confidence: 99%